(untitled) (Comparative & International Education Series, 2021)
This chapter reports the findings of a study based on structured interviews with key stakeholders of a private university in Poland (e.g., Rector, International Office, Students’ Union). This is a highly internationalized institution, with one quarter of all students being international. The main research questions were: 1) How has the COVID-19 pandemic impacted the operations of the International University? And 2) How did a relatively small and flexible university adapt to the national and international students’ needs in the first phase of the pandemic? This topic is worth pondering, as the media have reported that some students in Poland were asked to leave their student accommodation immediately, felt misinformed, and had problems crossing the border safely.